Treatment of Cutaneous Angiosarcoma of the Face: Efficacy of Combined Chemotherapy and Radiotherapy. Issue 5 (September 2013) - Ravo, Vincenzo; Falivene, Sara; De Chiara, Annarosaria; De Palma, Giampaolo; Pizzolorusso, Antonio; Di Franco, Rossella; Muto, Paolo; Apice, Gaetano
Introduction: Cutaneous angiosarcoma (AS) is a rare form of soft tissue sarcoma. It is aggressive and has a poor prognosis. The aim of our report is to show that with combined chemotherapy and radiotherapy it is possible to obtain good results in terms of local control, complete response, and aesthetic outcome. Case report: We present the case of a 60-year-old man affected by AS covering the entire surface of the nose. Surgery, although indicated, was excluded because it was considered mutilating and would give a poor cosmetic result. The patient was treated with chemotherapy consisting of paclitaxel 80 mg/m 2 for 6 cycles followed by radiotherapy at a dose of 50 Gy. Then 3 additional cycles of chemotherapy were administered according to the same scheme. A complete response was obtained. At 40 months after treatment, the patient did not show any signs of late toxicity, all lesions had disappeared, and all laboratory tests were negative. Conclusions: Our experience shows that concomitant chemoradiotherapy can be delivered safely and can be tolerated with low toxicity and good results in terms of local control and complete response. We obtained an excellent aesthetic result with improvement of the patient's quality of life.